2021
DOI: 10.1302/2058-5241.6.200045
|View full text |Cite
|
Sign up to set email alerts
|

The use of low intensity pulsed ultrasound in the foot and ankle

Abstract: Low intensity pulsed ultrasound (LIPUS) therapy has demonstrated clinical effectiveness in achieving union in a variety of fracture situations. Few studies have investigated the effectiveness of LIPUS therapy in foot and ankle surgery. The overall rate of union in all published studies relating to the use of LIPUS in a variety of foot and ankle fracture and fusion situations is 95%. Some studies suggest lower healing rates (~ 67%) when LIPUS therapy is used to treat hindfoot fusion nonunion. A well-powered, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Many studies have proven that LIPUS therapy is an excellent conservative therapeutic approach for bone and cartilage tissues. 6 , 11 , 12 Among the non-surgical therapy alternatives for tendon injuries, the use of LIPUS is one of the most explored. However, no research demonstrating the efficacy of the treatment supported by in vivo investigations exists.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proven that LIPUS therapy is an excellent conservative therapeutic approach for bone and cartilage tissues. 6 , 11 , 12 Among the non-surgical therapy alternatives for tendon injuries, the use of LIPUS is one of the most explored. However, no research demonstrating the efficacy of the treatment supported by in vivo investigations exists.…”
Section: Discussionmentioning
confidence: 99%
“…A case report showed that a patient with a Jones fracture was treated with continuous cryotherapy and proprioceptive training, and the patient was able to walk normally with full weight bearing after 12 days of treatment [ 17 ]. Low-intensity pulsed ultrasound has been found to be effective in enhancing the healing rate of scars, including those in the foot and ankle [ 18 ]. Muscle strengthening exercises are crucial in rehab regimens, enhancing flexibility, stability, and confidence while also preventing falls and restoring mobility, thereby improving patients' quality of life and reducing discomfort [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a safe and non-invasive approach, LIPUS has shown great potential in tissue repair and resolution of inflammation in various diseases. [32][33][34][35] Of note, the therapeutic effects of LIPUS on cardiovascular diseases have been reported in recent years. [10][11][12][13][14] In our present study, we showed that LIPUS therapy provided a great benefit in both acute and chronic DOX injury models, including the improvement of cardiac contractile function, the attenuation of myocardial injury and cellular apoptosis, as well as the alleviation of oxidative stress and cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, effective and safe strategies remain limited. As a safe and non‐invasive approach, LIPUS has shown great potential in tissue repair and resolution of inflammation in various diseases 32–35 . Of note, the therapeutic effects of LIPUS on cardiovascular diseases have been reported in recent years 10–14 .…”
Section: Discussionmentioning
confidence: 99%